Women Entrepreneur’s Capability dan Pendapatan UMKM Industri Pariwisata Pada Masa Pandemi Covid-19 - Luluk Fadliyanti; Diswandi Diswandi; Baiq Saripta Wijimulawiani (Sekolah Tinggi Ilmu Ekonomi AMM, 2023)
The purpose of this study is to determine the influence of women entrepreneurs, capability on MSME income in the tourism industry on the island of Lombok through the digital economy. The digital economy focusing on social media is an intervening variable in this study that will link financial capability, human resources capability and technology capability to MSME income. The data used is primary data by distributing questionnaires directly to women entrepreneurs in Mataram city. and also using secondary data taken from Badan Pusat Statistik of West Nusa Tenggara Province and Dinas Koperasi Perindustrian dan Perdagangan of West Nusa Tenggara Province. This study uses quantitative analysis methods, with purposive sampling analysis techniques with a total sample of 100 MSME women entrepreneurs in the tourism industry. And using likert scale research instruments and Path Analysis tools, using PLS 3.0 to test hypotheses. The results of the analysis show that the variables Financial Capability and Human Capital Capability have an indirect or direct influence on the variables of MSME Income in the tourism industry, while Technology Capability has no direct influence either directly on income or through social media intervening variables.